Gain and loss: Human and environmental wellbeing – drivers of Kilimanjaro’s decreasing biodiversity - Andreas Hemp; Mieko Miyazawa; Pekka Hurskainen (PLoS ONE, 2025)
Tropical mountains such as Kilimanjaro are biodiversity hotspots providing ecosystem services for millions of people, but many are under great pressure. Effective policies to halt biodiversity loss require an understanding of which anthropogenic factors are the main direct causes. While previous research focused mainly on climate change and on the effects rather than the causes, we investigated the effects of multiple drivers on biodiversity. The focus is on floristic and vegetation diversity, as vegetation is closely related to the diversity of other taxa and plays a fundamental role in ecosystem functioning. We show that land-use change caused by rapid population growth was the main direct driver on Kilimanjaro between 1911 and 2022, when 75% of natural species per km 2 disappeared from the lower slopes. Climate change, on the other hand, had no apparent influence on the observed trends in biodiversity. The significant increase in traditional and diverse agroforestry and the establishment of protected areas show possibilities for mitigation. Kilimanjaro is thus an example of the challenges of global change, but also of the prospects and opportunities for other tropical regions.